2019
DOI: 10.1186/s42358-019-0058-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in female juvenile idiopathic arthritis patients

Abstract: Objective: To evaluate sexual function female adolescents and young adults with juvenile idiopathic arthritis (JIA) and healthy controls. Methods: After exclusion, 21 female adolescent and young JIA patients and 25 healthy controls were selected for this study. Sexual function was assessed by the Sexual Quotient Questionnaire for Females (SQQ-F) score, which is a validated tool and adapted for Brazilian Portuguese language. Demographic data, JIA clinical/laboratory parameters and treatment were also assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“… 13 Both instruments were developed in Brazilian Portuguese as self-reported questionnaires to evaluate several sexual domains ( Table 3 ), 12 , 13 and currently they are used for population surveys in different scenarios. 14 , 15 Data were analyzed in questions to be answered in a Likert scale fashion (0 = never to 5 = always), usually expressing the satisfaction level or frequency of a specific event, contemplating the sexual response cycle phases. In the end, a score can be disclosed for each sexual domain, or indeed the overall quality of sexual life can be declared as a total score, ranging from 0 to 100 points.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… 13 Both instruments were developed in Brazilian Portuguese as self-reported questionnaires to evaluate several sexual domains ( Table 3 ), 12 , 13 and currently they are used for population surveys in different scenarios. 14 , 15 Data were analyzed in questions to be answered in a Likert scale fashion (0 = never to 5 = always), usually expressing the satisfaction level or frequency of a specific event, contemplating the sexual response cycle phases. In the end, a score can be disclosed for each sexual domain, or indeed the overall quality of sexual life can be declared as a total score, ranging from 0 to 100 points.…”
Section: Methodsmentioning
confidence: 99%
“… 13 Table 3 demonstrates the standardization of sexual performance classification, according to FSQ and MSQ Scores, and that a total score of below 62 indicates an unfavorable sexual performance. 12 , 13 , 14 , 15 The expected time for the participant to complete the online survey was around 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, one comparative study of young adult women with JIA and healthy controls suggested only a minimal impact. However, this needed to be confirmed by further multicenter studies [ 28 ]. Meanwhile, studies on the current understanding and delivery of SH education in rheumatology practices seem scant.…”
Section: Introductionmentioning
confidence: 99%